Nursing leaders' perspectives on research in specialist health services: A descriptive study - Kari Toverud Jensen; Peter Forde Hougaard; Unni Knutstad (Wiley, 2023)
Abstract Aim This study is to gain insight into how nursing leaders perceive their contribution to research‐based knowledge in hospital settings. Design The study has a qualitative descriptive design. Methods Nine nursing leaders were interviewed. Data were analysed based on Braun and Clarke's thematic analysis. Results Three themes were developed: the primacy of management and practicalities, delegated responsibility and lack of research competence. Even though the nurse leaders wish to be professional leaders, they seem to prioritize the day‐to‐day management. The nurse facilitators have been delegated, by the nurse leaders, the responsibility for the departments and the employees' professional development. The participants reported that neither their own leaders, the nurses, nor they themselves had the necessary knowledge or the interest in engaging in research. Conclusion There seems to be a lack of awareness, knowledge and priority of nursing research in nursing leadership and absence of a culture of research.